Synthesis of Ocean Observations Using Data Assimilation for Operational, Real-Time and Reanalysis Systems: A More Complete Picture of the State of the Ocean - Moore, Andrew M.; Martin, Matthew J.; Akella, Santha; Arango, Hernan G.; Balmaseda, Magdalena; Bertino, Laurent; Ciavatta, Stefano; Cornuelle, Bruce; Cummings, Jim; Frolov, Sergey; Lermusiaux, Pierre; Oddo, Paolo; et al. (Frontiers in Marine Science, 2019)
Ocean data assimilation is increasingly recognized as crucial for the accuracy of real-time ocean prediction systems and historical re-analyses. The current status of ocean data assimilation in support of the operational demands of analysis, forecasting and reanalysis is reviewed, focusing on methods currently adopted in operational and real-time prediction systems. Significant challenges associated with the most commonly employed approaches are identified and discussed. Overarching issues faced by ocean data assimilation are also addressed, and important future directions in response to scientific advances, evolving and forthcoming ocean observing systems and the needs of stakeholders and downstream applications are discussed.